Education of pediatric subspecialty fellows in transport medicine: a national survey - Mickells, Geoffrey E. (BMC Pediatr, 2017)
BACKGROUND: The transport of critically ill patients to children’s hospitals is essential to current practice. The AAP Section on Transport Medicine has raised concerns about future leadership in the field as trainees receive less exposure to transport medicine. This study identifies the priorities of pediatric subspecialty fellows, fellowship directors and nursing directors in transport medicine education. METHODS: Internet based surveys were distributed to fellows, fellowship directors and nursing directors of transport teams affiliated with ACGME-approved fellowships in Neonatal-Perinatal Medicine (NPM), Pediatric Critical Care Medicine (PCCM), and Pediatric Emergency Medicine (PEM). Data collection occurred November 2013 to March 2014. RESULTS: Four hundred and sixty-six responses were collected (357 fellows, 82 directors, 27 nursing directors): Six curricular elements were ranked by respondents: Transport Physiology (TP), Medical Control (MC), Vehicle Safety (VS), Medicolegal Issues (ML), Medical Protocols (MP) and State and Federal Regulations (SFR). Fellows and fellowship directors were not significantly different: TP (p = 0.63), VS (p = 0.45), SFR (p = 0.58), ML (p = 0.07), MP (p = 0.98), and MC (p = 0.36). Comparison of subspecialties found significant differences: PEM considered TP less important than NPM and PCCM (p < 0.001, p < 0.001), VS less important than NPM (p = 0.001). PEM viewed SFR and MC more important than PCCM (p = 0.006, p = 0.002); ML more important than PCCM and NPM (p = 0.001, p < 0.001). PCCM ranked MC more important than NPM (p = 0.004). Nursing directors considered TP less important than NPM and PCCM (p < 0.001, p = 0.002). CONCLUSIONS: When ranking curricular elements in transport medicine, fellows and fellowship directors do not differ, but comparison of subspecialties notes significant differences. A fellow curriculum in transport medicine will utilize these results. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12887-017-0780-5) contains supplementary material, which is available to authorized users.